Aged Garlic Supplementation Improves the Anxiety and Depressive-Like Behavioral Manifestations Induced by Maternal Separation in a Rodent Model (Bangladesh Pharmaceutical Journal, 2025)
Maternal separation (MS) is a commonly used paradigm in rodents that has been widely established as a model to study the long-term effects of early-life stress on brain function and behavior, eventually resulting in heightened anxious- and depressive-like behavior. The present study aimed to assess whether supplementation with aged garlic extract (AGE) could reduce the symptoms of adverse effects in mice. We used a battery of behavior tests such as forced swim test (FST), tail suspension test (TST), elevated plus maze (EPM) and open field test (OFT) to evaluate anxiety- and depressive-like behaviors. Our data demonstrated that aged garlic extract treatment markedly (p